2009
DOI: 10.3390/ijms10020507
|View full text |Cite
|
Sign up to set email alerts
|

Anomalously Strong Effect of the Ion Sign on the Thermochemistry of Hydrogen Bonded Aqueous Clusters of Identical Chemical Composition

Abstract: Abstract:The sign preference of hydrogen bonded aqueous ionic clusters Χ±(H 2 O) i (n =1-5, Χ = F; Cl; Br) has been investigated using the Density Functional Theory and ab initio MP2 method. The present study indicates the anomalously large difference in formation free energies between cations and anions of identical chemical composition. The effect of vibrational anharmonicity on stepwise Gibbs free energy changes has been investigated, and possible uncertainties associated with the harmonic treatment of vibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…We have chosen to hydrate the singly charged ions by three water molecules and the doubly charged ions with six water molecules to be certain that there are no errors due to electron detachment. The structure of the ion–water clusters have in several cases previously been identified and were extracted from the following publications: (Cl – )­(H 2 O) n from Nadykto et al, (NO 3 – )­(H 2 O) n from Liu et al, (NH 4 + )­(H 2 O) n from Pickard et al, and (SO 4 2– )­(H 2 O) n from Lambrecht et al In the case of the (Na + )­(H 2 O) 3 cluster, we were unable to find any literature structure, and it was therefore manually constructed. For details of the construction and configurational sampling of the monohydrate-ion–water clusters, the SI and the references cited therein.…”
Section: Methodsmentioning
confidence: 99%
“…We have chosen to hydrate the singly charged ions by three water molecules and the doubly charged ions with six water molecules to be certain that there are no errors due to electron detachment. The structure of the ion–water clusters have in several cases previously been identified and were extracted from the following publications: (Cl – )­(H 2 O) n from Nadykto et al, (NO 3 – )­(H 2 O) n from Liu et al, (NH 4 + )­(H 2 O) n from Pickard et al, and (SO 4 2– )­(H 2 O) n from Lambrecht et al In the case of the (Na + )­(H 2 O) 3 cluster, we were unable to find any literature structure, and it was therefore manually constructed. For details of the construction and configurational sampling of the monohydrate-ion–water clusters, the SI and the references cited therein.…”
Section: Methodsmentioning
confidence: 99%
“…Quantum chemistry calculations have also been used to investigate the underlying mechanism relevant to ion-induced nucleation for which sufficient experimental data exist on the thermochemistry of HSO 4 – -based and H 2 S 2 O 7 – -based ion clusters. Nadykto et al , showed that the sign preference in ion-induced nucleation, which manifests itself in water preferring to nucleate more efficiently on negatively charged ions, arises from the molecular structure of small charged clusters and can be explained and predicted by quantum chemical calculations. Furthermore, the stabilizing effect of ammonia on formation of negatively charged cluster hydrates is ruled out .…”
Section: Nucleation Of Nanoparticles In the Atmospherementioning
confidence: 99%
“…37 They have argued that cations are more effective nucleation enhancers than anions due to quantum effects that are included in their DFT model but neglected in empirical models. [37][38][39] The most significant limitation of both ab initio and mass spectrometry data is their relatively small range of accessible cluster sizes. Mass spectrometry data can only be obtained for clusters sufficiently stable to be found in measurable concentrations, while ab initio calculations for larger clusters require tremendous amounts of computational effort.…”
Section: Introductionmentioning
confidence: 99%